Association of serum 25-hydroxyvitamin D with sleep disorders in individuals with prediabetes and diabetes: a prospective cohort study - Liu, Guodong; Li, Huaxue; Ma, Yicheng; Shi, Yingzhou; Han, Junming; Li, Fei; Fang, Li; Tian, Shengyu; Cheng, Yiping (Frontiers in Endocrinology, 2025)
BackgroundSleep disorders are common globally and are linked to various adverse health outcomes, including cardiovascular disease, type 2 diabetes, and mental health conditions. Emerging evidence suggests a potential role of serum 25-hydroxyvitamin D (25(OH)D) in regulating sleep. Individuals with prediabetes and diabetes are at an increased risk of both vitamin D deficiency and sleep disorders, yet the relationship between these factors remains insufficiently studied. Utilizing data from the UK Biobank, this study aims to investigate the association between serum 25(OH)D concentrations and the risk of sleep disorders in individuals with prediabetes and diabetes.MethodsWe conducted a cross-sectional study of 81,533 participants (mean age 59.6 [SD 7.1] years, comprising 41,275 males [50.6%] and 40,278 females [49.4%]) from the UK Biobank, followed by a prospective study of 80,546 participants (mean age 59.6 [SD 7.1] years, comprising 40,513 males [50.3%] and 40,033 females [49.7%]) within the same cohort, focusing on individuals with prediabetes and diabetes. Baseline serum 25(OH)D concentrations were categorized into four groups: severe deficiency (<25.0 nmol/L), moderate deficiency (25.0–50.0 nmol/L), insufficiency (50.0–75.0 nmol/L), and sufficiency (≥75.0 nmol/L). Multivariable logistic regression and Cox proportional hazards models were used, adjusting for demographic, lifestyle, and health-related confounders.ResultsOver an average follow-up of 12.8 years, we documented 2,704 cases of sleep disorders and found that higher serum 25(OH)D concentrations were significantly associated with reduced sleep disorder risk. In fully adjusted models, sufficient serum 25(OH)D concentrations reduced sleep disorder risk by 48% in prediabetes (HR = 0.52; 95% CI: 0.41–0.65) and 52% in diabetes (HR = 0.48; 95% CI: 0.34–0.67). Subgroup analysis found that adequate vitamin D concentrations were associated with improved sleep health especially in people ≤60 years of age, women, BMI≥30kg/m², and those who had never smoked.ConclusionThis study provides strong evidence that higher serum 25(OH)D concentrations are associated with a reduced risk of sleep disorders in individuals with prediabetes and diabetes. These findings suggest that maintaining adequate vitamin D concentrations may offer a potential strategy to improve sleep health in this population.